ChemInform Abstract: High Performance Na‐Doped Lithium Zinc Titanate as Anode Material for Li‐Ion Batteries. Issue 34 (August 2015) - Chen, Wei; Zhou, Zhengrong; Wang, Rongrong; Wu, Zhengtao; Liang, Hanfeng; Shao, Lianyi; Shu, Jie; Wang, Zhoucheng
Abstract Li2‐xNaxZnTi3O8 (x = 0—0.20) are prepared by calcination of stoichiometric amounts of ball milled (12 h) nano‐TiO2, Li2CO3, Na2CO3, and Zn(OAc)2 (750 °C, 5 h).